Observation on the Book “A Short Summary of Handbook of Forty-Seven Stones of Totgor Astrology” - Damdinsuren, Davaasuren (Tibetan Studies, 2024)
This is a summary of the handbook of the forty-seven stones of Totgor astrology by Luvsandagdan, a disciple of Shiva Shirat. The book “Bolor toli” has a length of 14 and 28 pages and was written in 1905 according to our assumption. It consists of a devotional poem with the author’s oath, a final poem with information about the author and blessings, and has the following structure: 1. The twelve years (lines 2-4 of page 2a) 2. The five entities of wood, fire, earth, metal, and water (lines 4 of page 2a, lines 1-3 of page 2b) “Тотгорын зурхай дөчин долоон чулууны гарын авлагын товч хураангуй болор толь” хэмээхэд хийсэн ажиглалт Хураангуй: Тус өгүүлэлд, Шива ширээтийн шавь Лувсандагдангийн бичсэн “Тотгорын зурхай дөчин долоон чулууны гарын авлагын товч хураангуй Болор толь” хэмээх төвөд хэлээр бичсэн, гар бичмэл, 28 тал судрыг төвөд хэлнээс орчуулан, судалгааны эргэлтэд оруулсан болно. Түлхүүр үг: төвөд хэлт утга зохиол, зурхайн эх сурвалжууд, тотгорын зурхай